Water, Water Quality, and Pond Bottom Soil Management in Ugandan Aquaculture - Naigaga, Shamim; Boyd, Claude E.; Molnar, Joseph J.; Walakira, John (National Fisheries Resources Research Institute (NaFIRRI), 2013)
Fisheries production from lakes and other natural waters in Uganda are declining and expansion of the aquaculture sector is needed to increase aquatic protein for human consumption. The present study was conducted to improve understanding of limitations imposed on aquaculture by the environmental factors of climate, soils, and water quality in Uganda. Although not optimum, the temperature regime in Uganda is conducive to year-around aquaculture in most areas. Rainfall is adequate to maintain water levels in ponds throughout the year in the Western, Eastern, and Central regions. In the Northern region, it would be necessary to store water in farm reservoirs to use for maintaining water levels during the driest months. There is a tendency towards drought in Uganda, and severe droughts could cause water shortages for aquaculture. Water quality was generally suitable in all four regions for fish production. The main limitation would be the need to lime ponds in some areas in all regions. Unfortunately, the liming materials available in the country are of poor quality, and the agricultural limestone currently used by fish farmers is particularly low in quality. There is an urgent need to find better sources of liming materials and begin an effort to promote liming in Ugandan aquaculture. The main limitations of soils for pond sites were coarse soil texture, steep terrain in some areas, and a widespread problem of low acidity. Of course, as in any country, each prospective pond site must be examined for its suitability. There also is cage culture in several lakes in Uganda; Lake Victoria and Lake Albert appear to be the best lakes in which to consider expansion of cage culture operations. In summary, there does not appear to be insurmountable environmental restrains to expanding aquaculture production in Uganda. The major issues relate to selecting good sites for ponds and to finding a source of good quality liming material.
Keywords: Water; Water Quality; Pond Bottom Soil Management; Ugandan Aquaculture